2020
DOI: 10.1111/nhs.12779
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological interventions to improve the psychological well‐being of women accessing abortion services and their satisfaction with care: A systematic review

Abstract: How women perceive and experience abortion impacts their subsequent psychological well-being. This systematic review evaluated nonpharmacological interventions designed to support women undergoing abortion services and improve their psychological wellbeing and satisfaction with care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Despite the critical role of support to women accessing abortion, little attention has been paid to the psychosocial aspects of care [13]. A recently published systematic review found that in the past ten years, only ten experimental studies had been conducted to address the psychological needs of women undergoing abortion [14]. All interventions used a single-component design (e.g., music therapy, information support, or implementation of mandated waiting or counselling policies), and none were informed by a theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the critical role of support to women accessing abortion, little attention has been paid to the psychosocial aspects of care [13]. A recently published systematic review found that in the past ten years, only ten experimental studies had been conducted to address the psychological needs of women undergoing abortion [14]. All interventions used a single-component design (e.g., music therapy, information support, or implementation of mandated waiting or counselling policies), and none were informed by a theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…All interventions used a single-component design (e.g., music therapy, information support, or implementation of mandated waiting or counselling policies), and none were informed by a theoretical framework. Con icting outcomes and methodological limitations hindered conclusions about which intervention could reasonably be adopted to improve women's psychological well-being [14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the critical role of support to women accessing abortion, little attention has been paid to the psychosocial aspects of care [ 13 ]. A recently published systematic review found that in the past ten years, only ten experimental studies had been conducted to address the psychological needs of women undergoing abortion [ 14 ]. All interventions used a single-component design (e.g., music therapy, information support, or implementation of mandated waiting or counselling policies), and none were informed by a theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…All interventions used a single-component design (e.g., music therapy, information support, or implementation of mandated waiting or counselling policies), and none were informed by a theoretical framework. Conflicting outcomes and methodological limitations hindered conclusions about which intervention could reasonably be adopted to improve women’s psychological well-being [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research team conducted a systematic review to synthesize and integrate evidence surrounding the design and effectiveness of existing interventions in promoting the psychological wellbeing of women experiencing abortion [19]. The systematic review reported inconsistencies in the published literature with limited available high-quality evidence [19].…”
Section: Introductionmentioning
confidence: 99%